2023
DOI: 10.1007/s00259-023-06256-7
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of glucose analogue with SGLT2 affinity predicts response effectiveness to sodium glucose transporter 2 inhibitors in patients with type 2 diabetes mellitus

Barbara Katharina Geist,
Helmut Brath,
Lucia Zisser
et al.

Abstract: Purpose Sodium-glucose cotransporter 2 inhibitor (SGLT2i) regulation, developed as treatment for patients with type 2 diabetes, can be imaged with the glucose analogue alpha-methyl-4-deoxy-4-[18F]fluoro-d-glucopyranoside (Me4FDG), a positron emission tomography (PET) tracer with a high affinity for SGLT1 and SGLT2 proteins. With regard to therapy effectiveness, we aimed to investigate whether clinical parameters or Me4FDG excretion could predict response to SGLT2i in patients with type 2 diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 19 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…Also recent findings in rodents suggest to use this tracer for renal examinations [ 19 ]. In particular, it was shown that renal uptake can be altered due to SGLT inhibition treatments, which was also already implied by our study [ 10 ]. Moreover, the animal data found that Me4FDG can be used to determine the effects of SGLT inhibition in the digestive tract [ 20 ], suggested to be used as patient selection tool for diabetic patients designated for SGLT inhibition therapy.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Also recent findings in rodents suggest to use this tracer for renal examinations [ 19 ]. In particular, it was shown that renal uptake can be altered due to SGLT inhibition treatments, which was also already implied by our study [ 10 ]. Moreover, the animal data found that Me4FDG can be used to determine the effects of SGLT inhibition in the digestive tract [ 20 ], suggested to be used as patient selection tool for diabetic patients designated for SGLT inhibition therapy.…”
Section: Discussionsupporting
confidence: 87%
“…Herein, we investigated clinical safety, biodistribution and radiation dosimetry of [ 18 F]Me4FDG in 5 healthy adult volunteers with no history of oncologic or endocrinologic diseases While this tracer demonstrated no side effects in patients with type 2 diabetes in a 3-month longitudinal study [ 10 ], to our knowledge it has not yet been systematically studied in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations